2016
DOI: 10.1080/00365521.2016.1200141
|View full text |Cite
|
Sign up to set email alerts
|

Low colectomy rate five years after diagnosis of ulcerative colitis. Results from a prospective population-based cohort in Sweden (ICURE) diagnosed during 2005–2009*

Abstract: Five years after diagnosis of ulcerative colitis, 5.3% had been subjected to colectomy and two patients (0.38%) had died because of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 30 publications
(34 reference statements)
4
18
0
Order By: Relevance
“…The overall incidence of UC in Europe, North America and Oceania is independent of gender. In CD, less consistent findings have been reported, with some cohorts suggesting a female predominance in the incidence of CD and others failing to find any gender difference whatsoever . In a pooled analysis of studies in the West, females predominated among CD patients from adolescence to middle‐age, while a higher risk of UC was found among males aged 45 years and older …”
Section: Clinical Features Of Ibdmentioning
confidence: 94%
See 3 more Smart Citations
“…The overall incidence of UC in Europe, North America and Oceania is independent of gender. In CD, less consistent findings have been reported, with some cohorts suggesting a female predominance in the incidence of CD and others failing to find any gender difference whatsoever . In a pooled analysis of studies in the West, females predominated among CD patients from adolescence to middle‐age, while a higher risk of UC was found among males aged 45 years and older …”
Section: Clinical Features Of Ibdmentioning
confidence: 94%
“…In Western Europe, North America and Oceania, the average age of onset in adult incident cases was a median 31–34 years . In both CD and UC, incidence peaked in the age interval 20–30 years; however, a second peak between the ages of 60–79 years was reported in UC.…”
Section: Clinical Features Of Ibdmentioning
confidence: 99%
See 2 more Smart Citations
“…A subsequent report based on a study period from 1989–2009 reported a colectomy rate for ulcerative colitis of 10% at 10 years . Prospective population cohort studies from Scandinavia for both ulcerative colitis and Crohn's also report a decrease in rate of colectomy . In a systematic review and meta‐analysis the progressively decreased risk of surgery for IBD was convincingly demonstrated for both ulcerative colitis and Crohn's disease.…”
Section: Colectomy For Ibdmentioning
confidence: 99%